Automatic system of mutually invariant vector control of mixer technology state variables - Neydorf, Rudolf A.; Mohsen, Mohammed Neamah (Advanced engineering research (Rostov-na-Donu, Russia), 2016)
The work objective is to improve the automation efficiency of the technological processes of the chemical industry and the related industries. A typical for the industry solution preparation process is considered; and the task of developing a vector control law, effective in terms of both intensity or speed and cross-invariance of the management processes of various technological variables, is solved. To cope with this task, the approach to the control laws synthesis based on the desired characteristics of the synthesized control system is taken. A mathematical model of the quasi-optimal speed control is used to construct the desired mathematical model of the controlled machine for the solution preparation. The synthesis is resulted in a rather complex non-linear vector control law which, however, provides all the properties inherent in the paradigm of its creation and implementation. Simulation modeling of a multistage automatic control system with the implementation of the synthesized laws is carried out, as well as the research of the constructed model. This allows fully confirm an absolute control autonomy of the outflow solution level in the unit and of its concentration. Besides, the independence of the controlled variables from the changing load - flow fluid preparation - is established. The results obtained are intended for the implementation in the chemical technology and the related industries (food processing, oil refining, etc.). The materials and the research results presented show that for an effective synthesis of the vector control laws of nonlinear multiply connected objects, the method of reference mathematical models can be applied along with the quasi-optimization speed performance of these laws.